2018
DOI: 10.1177/0333102418769948
|View full text |Cite
|
Sign up to set email alerts
|

Presence of vestibular symptoms and related disability in migraine with and without aura and chronic migraine

Abstract: Objective To assess the presence and handicap due to vestibular symptoms in three subgroups of patients with migraine and controls. Methods Women between 18-55 years old were diagnosed by headache specialists and stratified as migraine with aura (n = 60), migraine without aura (n = 60), chronic migraine (n = 60) and controls (n = 60). Information regarding demographics, headache and vestibular symptoms were collected in this cross-sectional study. The self-perceived handicap related to vestibular symptoms was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 42 publications
5
71
0
8
Order By: Relevance
“…Even after this exclusion, the results still show that there is an association between migraine and vestibular symptoms, which is more common in patients with chronic headache; this nding is consistent with the results of previous studies (8,9). However, the chronicity of migraine was not accounted for in the proposed vestibular migraine criteria (7,9), and it is poorly explored by studies on the topic (9,21,22). The correlation between vestibular symptoms and headache needs to be further researched.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Even after this exclusion, the results still show that there is an association between migraine and vestibular symptoms, which is more common in patients with chronic headache; this nding is consistent with the results of previous studies (8,9). However, the chronicity of migraine was not accounted for in the proposed vestibular migraine criteria (7,9), and it is poorly explored by studies on the topic (9,21,22). The correlation between vestibular symptoms and headache needs to be further researched.…”
Section: Discussionsupporting
confidence: 92%
“…The association between vestibular symptoms and migraine has been established in previous studies (9,14,15), which led the International Headache Society and the International Vertigo Society to propose research criteria for vestibular migraine (16). Our previous studies showed that 10% of migraine patients ful lled the research criteria for vestibular migraine (11,17).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…29,30 When vestibular symptoms were assessed in patients with migraine using the Dizziness Handicap Inventory Questionnaire, more than two-thirds reported vestibular symptoms, compared with 12% in controls. 31 Patients with MA and chronic migraine were significantly more likely to have vestibular symptoms than patients with migraine without aura (MoA). Vestibular symptoms can occur during headaches, but often occur during headache-free intervals.…”
Section: Clinical Featurementioning
confidence: 99%
“…In addition, duration of VM episodes are notoriously variable, where intense episodes may occur on the order of minutes to hours to days [9], or as constant and lingering symptoms of less intensity but lasting months or years [16]. Recently, emerging evidence confirms vestibular symptoms from vestibular migraine can to be chronic [17]. The initial episodes of VM can be frighteningly similar with the acute vestibular syndrome or an acute but transient vestibular syndrome (<24 hours).…”
mentioning
confidence: 99%